E-085 Good Baseline Angiographic Collateral Flow Correlates with Successful Recanalization and Clinical Outcome after Endovascular Treatment for Acute Ischemic Stroke Within 24 Hours from Onset. (29th July 2016) - Seo, J; Kim, E; Jeong, H
Abstract : Background: Recanalization status is the strongest predictor of clinical outcome in patients undergoing endovascular treatment (EVT). Although the time to reperfusion remains crucial even with EVT, the previous meta-analysis demonstrated that recanalization up to 24 hours after acute ischemic stroke (AIS) onset is strongly associated with improved functional outcomes and reduced mortality. We evaluated the relationships among angiographic collateral flow, successful recanalization, and clinical outcome after EVT in patients experiencing AIS within 24 hours of onset. Methods: We assessed patients were experiencing acute anterior circulation ischemic stroke who underwent EVT between 2011 and 2015. Patients with large artery occlusion of anterior circulation and clinical diagnosis of AIS, within 24 hours of first found abnormal time (FAT), were included in the study. Results: One hundred seventy-three patients met the inclusion criteria. Mean age was 68.3 ± 12.6 years, and median National Institutes of Health Stroke Scale score was 14 (range, 5–29). Median time from FAT to arrival was 92 minutes. Overall successful recanalization, defined by the Modified Thrombolysis In Cerebral Infarction scale grade 2 b-3, was achieved in 65.3% of patients, and good clinical outcome, as defined by the modified Rankin Scale (mRS 0–2), was achieved in 47.4% of patients. For successful r the angiographic collateral grade was the independent factor. In multiple logistic regression analysis, the angiographic collateral grade was independently associated with clinical outcome after adjusting for other variables (odds ratio, 5.96; 95% CI, 1.76–20.19). Conclusions: Our data showed that angiographic collateral grade was a strong independent predictor of successful recanalization after EVT and good clinical outcome in AIS patients when applied up to 24 hours from FAT. Consequently, the good angiographic collateral flow may help predict successful recanalization and better clinical outcomes after EVT in patients with AIS. Disclosures: J. Seo: None. E. Kim: None. H. Jeong: None.